Alternative catalytic materials : carbides, nitrides, phosphides and amorphous boron alloys - Hargreaves, J. S. J.; McFarlane, Andrew R.; Laassiri, Said (RSC catalysis series ;, 2018)
An important reference for researchers and industrialists working in heterogeneous catalysis and materials chemistry.